Germination and growth of Sterculia colombiana in Arosemena Tola, Napo, Ecuador - Abril-Saltos, Ricardo Vinicio; Villacis-Estrada, Evelyn Aracelly; Tapuy-Andy, Micela Delsy; Pillco-Herrera, Briyidt Maryeli; Quishpe-Lopez, Jonny David; López-Adriano, Katherine Pamela (Agronomía Mesoamericana, 2023)
Introduction. The Amazon region has a great plant diversity, but studies on their propagation and growth have been carried out in few species. Objective. To evaluate the in situ and ex situ germination of Sterculia colombiana and its growth characteristics after planting in ground covers of primary forest and intervened areas. Materials and methods. The study was carried out in Napo, Ecuador, in the period 2019-2020. The germination of S. colombiana was characterized in the variables: days and percentage to emergence, plant height, stem diameter and number of leaves, under greenhouse conditions and planted at the collection site. The plants obtained in the germination test were transplanted to a ground cover of primary forest (in situ) and an intervened area with replacement vegetation (ex situ). Linear, quadratic, cubic, exponential, and logarithmic growth models for stem height and diameter were evaluated. The air and soil temperature and the physical-chemical characteristics of the soil were recorded. An analysis of variance was performed to determine differences in growth and survival between the plantation sites and between the plants obtained in the in situ and ex situ tests. Results. The seedlings obtained from greenhouses reported fewer days to emergence and higher values in the rest of the variables evaluated than those grown in situ. The plants developed in the different evaluated covers, without significant differences in growth at the end of the study, only a significant correlation at 5 % between stem diameter and air temperature was reported. Conclusions. Sterculia colombiana germinated in a greenhouse and developed in the transplant sites, without this influencing its growth. Temperature was the only factor that reported significant correlations with growth at the end of the evaluation period.